Business Cycles and Compositional Variation in U.S. Unemployment - Jaap H. Abbring; Gerard J. van den Berg; Jan C. van Ours (Tinbergen Institute, 1997)
In the past decades several features of U.S. unemployment dynamics have been investigated empirically. The original focus of research was on the duration of unemployment. In later studies the cyclicality of incidence and duration, compositional effects and duration dependence of the exit rate out of unemployment have been investigated. Unlike the partial approach of previous studies this paper takes all elements of unemployment dynamics simultaneously into account. We find that cyclical fluctuations in unemployment are driven by variations in the incidence, individual exit probabilities and the composition of the inflow into unemployment. We also find negative duration dependence of the unemployment exit rate which can be attributed to employers ranking workers according to the length of their unemployment spell.
Keywords: E32; J64; E24; 330; Business Cycles; Cycle; Unemployment; Arbeitslosigkeit; Konjunktur; USA